2014
DOI: 10.1074/jbc.m114.593210
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Adipocytes Promote Melanoma Cell Growth by Activating the Akt Signaling Pathway

Abstract: Background: Fatty acids affect cancer growth. Results: Melanoma in co-cultivation with subcutaneous adipocytes has an elevated level of palmitic acid that promotes melanoma growth by activating Akt signaling in a PTEN-independent manner. Conclusion: Subcutaneous adipocytes may be an exogenous source of palmitic acid for melanoma growth. Significance: Targeting an exogenous supply of palmitic acid suggests a novel therapeutic in melanoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 48 publications
7
57
0
Order By: Relevance
“…For example, palmitic acid negatively controls fibroblast function in the dermis . In addition, subcutaneous adipocyte‐derived palmitic acid enhances melanoma proliferation . Besides the regulation of fibroblasts and melanomas, our results indicate that palmitic acid induces REG3A expression in the HaCaT keratinocyte cell line and in normal human keratinocytes (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…For example, palmitic acid negatively controls fibroblast function in the dermis . In addition, subcutaneous adipocyte‐derived palmitic acid enhances melanoma proliferation . Besides the regulation of fibroblasts and melanomas, our results indicate that palmitic acid induces REG3A expression in the HaCaT keratinocyte cell line and in normal human keratinocytes (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, CAF-derived EV transport metabolites, such as amino acids, lipids, and TCA cycle intermediates, to tumor cells, which serves as triggers for central carbon metabolism (Zhao et al, 2016). Even though we know FA are released by adipocytes in response to tumor secretions for transfer to melanoma cells (Kwan et al, 2014;Zhang et al, 2018), we reveal that naïve adipocytes, that have never encountered tumor secretions, can also convey lipids to cancer cells through EV. Previous studies had focused on the transfer of free FA from adipocytes to tumor cells and the role of FA transporters in their uptake.…”
Section: Discussionmentioning
confidence: 82%
“…There also are reports about saturated fatty acid C16:0 inhibiting proliferation through an autophagic mechanism in cancer cells . Kwan et al reported the opposite observation, that C16:0 promoted melanoma growth by activating Akt signaling in a phosphatase and tensin homolog–independent manner . On the other hand, unsaturated fatty acid C18:1 was reported to stimulate tumor growth through stabilization of β‐catenin .…”
Section: Discussionmentioning
confidence: 99%